Therapeutic Measures for the Novel Coronavirus: A Review of Current Status and Future Perspective - Shahverdi, Mahshid; Darvish, Maryam (Current Molecular Medicine, 2021)
The coronavirus disease 19 (COVID-19) is a highly pathogenic and transmissible viral disease caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which originated in the city of Wuhan, Hubei Province, Central China and spread quickly around the world. The genome sequence of SARSCoV- 2 is phylogenetically related to bat-derived severe acute respiratory syndrome-like (SARS-like) coronaviruses; therefore bats could be the possible primary reservoirs. At present, there are no clinically approved vaccines or specific antiviral drugs for COVID- 19. However, several broad-spectrum antiviral drugs have been evaluated against COVID-19 in clinical studies and resulted in the improvement of patients. In this regard, other therapies such as antiviral drugs, antibodies, stem cells and plasma therapy are being studied. In the current study, we reviewed the emergence, pathogenicity and the genome structure of COVID-19 infection. The main focus of this study is on the therapeutic approaches that may be effective against SARS-CoV-2.
Keywords: SARS-CoV-2